“Yang Turun dari Langit dan Dampaknya” - dalam Kisah Para Rasul 2: Suatu Penelusuran Awal - Robby Chandra (Sekolah Tinggi Teologi Satyabhakti, Malang)
There has not been a study on the word ὥσπερ or ὡσεὶ (as) in the Book of Acts Chapter 2 by using Cognitive Linguistic Analysis theorem. Employing a method of interpretation based on such a theory, this study explores the meaning of the words. The hypothesis is the word ὥσπερ or ὡσεὶ.signify the complexity of the Holy Spirit’s role and the the Spirit’s agility. The finding shows that the Holy Spirit has multiple roles and agility beyond human word can describe. However, the Spirit’s main role is guide people to the Lordship of Christ, to transform the disciples to become courageous persons, people with the ability to communicate across borders, and to have agility in following God’s guidance to create real impacts in the society. The church that the Spirit dwells in and leads should possess such fluidity and multiple roles as the Holy Spirit.